2013
DOI: 10.12927/hcpol.2013.23478
|View full text |Cite
|
Sign up to set email alerts
|

High-Cost Users of Ontario's Healthcare Services

Abstract: Approximately 1.5% of Ontario' s population, represented by the top 5% highest cost-incurring users of Ontario' s hospital and home care services, account for 61% of hospital and home care costs. Similar studies from other jurisdictions also show that a relatively small number of people use a high proportion of health system resources. Understanding these high-cost users (HCUs) can inform local healthcare planners in their efforts to improve the quality of care and reduce burden on patients and the healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 3 publications
(2 reference statements)
1
68
0
Order By: Relevance
“…In Ontario, for example, 5% of healthcare users consumed 61% of hospital and home care spending (Rais et al 2013). A study of physician services utilization in British Columbia found that 5% of healthcare users consumed 30% of spending on physician services (Reid et al 2003).…”
Section: Résumémentioning
confidence: 99%
“…In Ontario, for example, 5% of healthcare users consumed 61% of hospital and home care spending (Rais et al 2013). A study of physician services utilization in British Columbia found that 5% of healthcare users consumed 30% of spending on physician services (Reid et al 2003).…”
Section: Résumémentioning
confidence: 99%
“…• A small proportion (5%) of patients with complex needs often account for as much as two-thirds of healthcare use and costs [30,31] Healthcare use in Canada is highly hospital-based and the care experience for patients and families is often reported as suboptimal [32].…”
Section: ) Rates Of Chronic Disease Are Increasingmentioning
confidence: 99%
“…It has been estimated that 5 percent of the United States population accounts for 49 percent of total health care spending [11]. Studies conducted in Canada have demonstrated that 5 percent of health care users are associated with 61 percent of hospital and home care expenses and 30 percent of physician service expenses [12] [13].…”
Section: Introductionmentioning
confidence: 99%